Development of Busy Book Learning Media Based on the Universe Theme to Develop English Vocabulary for Early Childhood of Kindergarten Group B at TK Amir Hamzah Medan - Raliza, Siti Nur; Damanik, Suri Handayani (International Journal of Applied and Advanced Multidisciplinary Research, 2023)
This research was carried out to determine the feasibility and practicality of busy book learning media based on the theme of the universe in developing the English vocabulary of early childhood in Kindergarten Group B. The research is R&D research using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Based on the research results, a score of 3.875 was obtained from media experts in the "Very Feasible" category. From media experts, a score of 2.9 was obtained in the "Decent" category in the first stage and a score of 3.8 was obtained in the "Very Feasible" category in the second stage. From the practicality test, a score of 3.7 was obtained in the "Very Feasible" category.